Translocation of long peptides by transporters associated with antigen processing (TAP) - Koopmann, Jens; Post, Markus; Neefjes, Jacques J.; Hämmerling, Günter J.; Momburg, Frank (European journal of immunology, 1996)
The major histocompatibility complex (MHC)-encoded transporters associated with antigen processing (TAP) translocate peptides from the cytosol into the lumen of the endoplasmic reticulum (ER) where they associate with MHC class I molecules. The length of class I-binding peptides is usually 8-11 amino acids, but examples of significantly longer peptides have been described. The preferred lengths and upper and lower size limits for peptides translocated by TAP have not been determined in detail because in the currently used test systems, peptides are subject to proteolytic degradation. In the present study, three sets of individual peptides or partially randomized peptide libraries ranging between 6 and 40 residues were used that contained a radiolabeled tyrosine and a consensus sequence for ER-specific N-glycosylation at opposite ends, thus ensuring that only nondegraded peptides were monitored in the transport/glycosylation assay. For three different transporters, rat TAP1/2a, rat TAP1/2u and hTAP, the most efficient ATP-dependent transport was observed for peptides with 8-12 amino acids. Hexamers and longer peptides of up to 40 amino acids were also translocated, albeit less efficiently. For two of the three sets of peptides analyzed, rat TAP1/2a showed a less stringent length selection than rat TAP1/2u and human TAP. The superior transport of the decamer of the TNKT. Y series was not due to faster degradation or less efficient glycosylation of shorter or longer length variants. A binding assay with TAP-containing microsomes revealed a high affinity for the radiolabeled decamer (KD = 580 nM), while other length variants were clearly inferior in their binding affinities. Thus, TAP binds and preferentially translocates peptides with a length suitable for binding to MHC class I molecules, but peptides that are considerably longer may also be substrates. About 105 peptide binding sites per cell equivalent of microsomes were determined, providing an estimate for the number of TAP complexes in the ER membrane.